An Inventory of the Equivalents of the Latest Foreign-Indonesian Term as a Means of Introducing Indonesian to Foreign Speakers - Sudaryanto, Hermanto & Dedi Wijayanti (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2018)
This study aims to invent the equivalent of the latest foreign-Indonesian term as a means of introducing Indonesian language to foreign speakers (BIPA). This research uses  qualitative approach. Data are obtained through reading and noting the equivalents of foreign-Indonesian terminology in dictionaries, books, and newspapers. This study uses content review techniques. The results of this study show about 5.800 equivalents of foreign-Indonesian terms covering eight study areas namely, (1) business and finance, (2) tourism, (3) sport, (4) property, (5) transportation and communication, (6) industry, (7) beauty and personal equipment, and (8) information and electronics.Keywords: inventory, equivalents of the latest foreign-Indonesian, BIPA